2005
DOI: 10.3842/sigma.2005.004
|View full text |Cite
|
Sign up to set email alerts
|

A System of n = 3 Coupled Oscillators with Magnetic Terms: Symmetries and Integrals of Motion

Abstract: Abstract. The properties of a system of n = 3 coupled oscillators with linear terms in the velocities (magnetic terms) depending in two parameters are studied. We proved the existence of a bi-Hamiltonian structure arising from a non-symplectic symmetry, as well the existence of master symmetries and additional integrals of motion (weak superintegrability) for certain particular values of the parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The purpose is to study new and interesting properties of the Kepler problem. In fact, it has been proved that if a dynamical vector field satisfies certain properties (existence of canonoid transformations [9,10] or existence of non-symplectic symmetries [27,28]) then it is Hamiltonian with respect to two different structures without satisfying necessarily the Nijenhuis condition.…”
Section: Structure and Purpose Of The Papermentioning
confidence: 99%
“…The purpose is to study new and interesting properties of the Kepler problem. In fact, it has been proved that if a dynamical vector field satisfies certain properties (existence of canonoid transformations [9,10] or existence of non-symplectic symmetries [27,28]) then it is Hamiltonian with respect to two different structures without satisfying necessarily the Nijenhuis condition.…”
Section: Structure and Purpose Of The Papermentioning
confidence: 99%
“…is called a master symmetry or a generator of symmetries of degree m = 1 for the Hamiltonian vector field X H [7,8,10,27,28].…”
Section: Recursion Operator and Master Symmetymentioning
confidence: 99%
“…This is well illustrated in Fig 1 . In differential geometric terms, Y j and Hj are called master symmetries for X i and master integrals, respectively, [7,8,10,27,28].…”
Section: Master Symmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of Smirnov's result to the classical Kepler problem is due to the possibility of transforming the action-angle coordinates connected with the spherical-polar coordinates to the Delaunay coordinates. In 2005, Rañada [51] proved the existence of a bi-Hamiltonian structure arising from a non-symplectic symmetry as well as the existence of master symmetries and additional integrals of motion (weak superintegrability) for certain particular values of two parameters b and k. In 2015, Grigoryev et al showed that the perturbed Kepler problem is a bi-Hamiltonian system in spite of the fact that the graph of the Hamilton function is not a hypersurface of translation, which goes against a necessary condition for the existence of the bi-Hamiltonian structure according to the Fernandes theorem [21,28]. They explicitly presented a few non-degenerate bi-Hamiltonian formulations of the perturbed Kepler problem using the Bogoyavlenskij construction of a continuum of compatible Poisson structures for the isochronous Hamiltonian systems [8].…”
Section: Introductionmentioning
confidence: 99%